Spatial engineering of a Co(OH)ₓ encapsulated p-Cu₂S/n-BiVO₄ photoanode : simultaneously promoting charge separation and surface reaction kinetics in solar water splitting - He, Bing (2021)
The photoelectrochemical (PEC) water splitting efficiency of a photoanode is restricted by charge recombination and sluggish reaction kinetics. Here, we demonstrated the spatial engineering of an ultrathin Co(OH)ₓ encapsulated p-Cu₂S/n-BiVO₄ photoanode for simultaneously enhancing charge separation and surface reaction kinetics in solar water splitting. Specifically, the separation efficiency of photoexcited charge carriers in the bulk was effectively improved due to the formation of a p-Cu₂S/n-BiVO₄ heterojunction, and the light-driven water oxidation reaction on the surface was further promoted because of the introduction of Co(OH)ₓ as an oxygen evolution catalyst (OEC) layer. As a result, the p-Cu₂S/n-BiVO₄ heterostructure yielded a largely enhanced charge separation efficiency of up to 79%, and a significant surface charge separation of 70% was achieved, attributed to the deposition of the Co(OH)ₓ cocatalyst. Furthermore, this synergistic effect in the photoanode gave rise to a remarkably enhanced photocurrent density of 3.51 mA cm⁻² at 1.23 V vs. the reversible hydrogen electrode. This spatial engineering provides an efficient strategy for the simultaneous improvement of internal and surface charge separation via dual modification, i.e., p-n heterojunction formation and OEC coating.